Graph-Theoretic Concepts in Computer Science 34th International Workshop, WG 2008, Durham, UK, June 30 -- July 2, 2008, Revised Papers - Broersma, Hajo; Erlebach, Thomas; Friedetzky, Tom; Paulusma, Daniel (Theoretical Computer Science and General Issues, 2008)
This book constitutes the thoroughly refereed post-conference proceedings of the 34th International Workshop on Graph-Theoretic Concepts in Computer Science, WG 2008, held in Durham, UK, in June/July 2008. The 30 revised full papers presented together with 3 invited paper were carefully reviewed and selected from 76 submissions. The papers feature original results on all aspects of graph-theoretic concepts in Computer Science, e.g. structural graph theory, sequential, parallel, and distributed graph and network algorithms and their complexity, graph grammars and graph rewriting systems, graph-based modeling, graph-drawing and layout, diagram methods, and support of these concepts by suitable implementations.